I am Pilgrim : a thriller - Hayes, Terry, 1951- (New York : Emily Bestler Books/Atria Books, 2014)
Pilgrim is the code name for a world class and legendary secret agent. His adversary is known only as the Saracen. As a young boy, the Saracen saw his dissident father beheaded in a Saudi Arabian public square, creating a burning desire to destroy the special relationship between the US and the Kingdom. When a woman's body is found in a seedy hotel near Ground Zero, the techniques are pulled from a cult classic of forensic science that Pilgrim wrote under a pen name. In offering the NYPD assistance with the case, Pilgrim gets pulled back into the intelligence underground.
Keywords: Fiction